THE USE OF CONTEXTUAL TEACHING AND LEARNING (CTL) AND VISUAL DICTIONARY TO IMPROVE THE DEAF STUDENTS’ ABILITY IN WRITING SHORT FUNCTIONAL TEXT AT TENTH GRADE STUDENTS OF SMA NEGERI LUAR BIASA LUBUKLINGGAU - Astri Riance (ELTE Journal (English Languange Teaching and Education), 2013)
ABSTRACTThe title of this study was “The use of contextual teaching and learning(CTL)And visual dictionary to improve the deaf students’ ability in writing short functional text at tenth grade students of SMA Negeri luar biasa lubuklinggau”. The problems of this study were: 1) How can Contextual Teaching and Learning (CTL) and visual dictionary improve the tenth grade students’ ability in writing short functional text of SMA Negeri Luar Biasa Lubuklinggau? 2) What are thestudents’ attitude in learning writing short functional text by using Contextual Teaching and Learning Method and visual dictionary? The objectives of this study were: 1) to improve the deaf students’ ability in writing short functional text byusing Contextual Teaching Learning (CTL) method and visual dictionary 2) To find out students’ attitude in learning writing short functional text by using Contextual Teaching and Learning Method and Visual Dictionary 3) To improvean interactive and interesting, teaching learning process and enhance students’ ability in learning language, so that they can apply their knowledge in their life. This study used classroom action research method which consisted three cycles. The technique for collecting the data were, test, observation and questionnaire.Key Words: Contextual Teaching and Learning, Visual Dictionary, Ability, Writing Short Functional Text.